Offspring's risk for suicidal behaviour in relation to parental death by suicide: systematic review and meta-analysis and a model for familial transmission of suicide. (March 2022) - Calderaro, Mara; Baethge, Christopher; Bermpohl, Felix; Gutwinski, Stefan; Schouler-Ocak, Meryam; Henssler, Jonathan
Abstract : Background: Exposure to parental suicide has been associated with increased risk for suicide and suicide attempts, although the strength of this association is unclear as evidence remains inconsistent. Aims: To quantify this risk using meta-analysis and identify potential effect modifiers. Method: A systematic search in PubMed, PsycInfo and Embase databases to 2020 netted 3614 articles. Inclusion criteria were: observation of history of parental death by suicide, comparison with non-exposed populations and definition of suicide and suicide attempt according to standardised criteria. We focused on population-based studies. The primary outcome was the pooled relative risk (RR) for incidence of suicide attempt and suicide in offspring of a parent who died by suicide compared with offspring of two living parents. Additionally, we compared the RR for attempted and completed suicide after parental suicide with the RR for attempted and completed suicide after parental death by other causes. Results: Twenty studies met our inclusion criteria. Offspring exposed to parental suicide were more likely to die by suicide (RR = 2.97, 95% CI 2.50–3.53) and attempt suicide (RR = 1.76, 95% CI 1.58–1.96) than offspring of two living parents. Furthermore, their risk of dying by or attempting suicide was significantly higher compared with offspring bereaved by other causes of death. Conclusions: The experience of losing a parent to suicide is a strong and independent risk factor for suicidal behaviour in offspring. Our findings highlight the need for prevention strategies, outreach programmes and support interventions that target suicide-related outcomes in the exposed population.